(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of the study was to compare the selected physical and physiological parameters such as cardio respiratory endurance and resting pulse rate between obese and non-obese men. To achieve this purpose of the study, thirty men obese students and thirty men non obese students study in the Pachayappa’s College, Chennai, Tamilnadu, India were selected as subjects were ranged from 17 to 24 years. Among the physical fitness and physiological components the following variables namely cardio respiratory endurance and resting pulse rate were selected. And they were tested by using Cooper’s 12 min Run walk and Radial Pulse. The data were collected on selected criterion variables and they were statistically analysed by using independent‘t’ ratio. In all the cases, .05 level of confidence was fixed to test the significance. The results of the study showed that there was a significant difference between obese men and non-obese men on selected criterion variables such as cardio respiratory endurance and resting pulse rate.